"New" Military History of the First Word War. Achievements and Limits. - Hutečka, Jiří (Dějiny – teorie – kritika, 2018)
Over recent decades, “new military history” has become a mainstream concept in the historical study of warfare. The article attempts to summarize how this concept has changed our understanding of the First World War, including all the main areas of research it has covered over the years, and focuses on the issue of a “missing link” in the study of conflicts through the lenses of both “new” and “old” military histories – that is, that violence and combat, which are the ultimate focus of every war effort, remain largely left out of the picture current historiographical work paints. Identifying this problem within the context of the historiography of the First World War, the text offers a brief insight into its origins and suggests some possible remedies.